Paul Revere's ride - Troupe, Thomas Kingsley; Tejido, Jomike (2017)
No one knows history better than these two special flies. Hang on to your hat as they share this story of secret meetings, galloping hooves, and danger around every corner: the beginnings of America's fight to become a country.
Includes bibliographical references and index.
Grades K-3.
Keywords: Revere, Paul, -- 1735-1818 -- Juvenile literature; Statesmen -- Massachusetts -- Biography -- Juvenile literature; Massachusetts -- Biography -- Juvenile literature; Massachusetts -- History -- Revolution, 1775-1783 -- Juvenile literature